CELENGAN UANG KOIN BERBASIS ARDUINO - Kunanti, Ananda; Yuni Setialoka; Ocsirendi; Sulistyo, Eko (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2024)
In today's economic system, money is an important medium of exchange and is used as a means of payment for transactions of goods and services as well as debt repayment. Coins are a form of money available in Indonesia in denominations of 100, 200, 500, and 1,000 rupiah. Counting and sorting coins in large quantities can be very tiring and time-consuming. For this reason, it is necessary to conduct research to make a piggy bank as a coin sorter and counter at a more affordable cost, using simple and easily available components. This system will use a TCRT5000 sensor to detect the diameter of the coin to determine its fraction. Sorting is done by directing the coin to the hole corresponding to its diameter. Counting is done with an Arduino Uno, which also controls the display on a 16x2 LCD to show the fractions and total coins detected.